Odiseo, Gengi, el Cid y Gorba Dikko: soberbia épica, violencia verbal y frontera acuática - José Manuel Pedrosa (Atalaya)
Analysis of episodes of verbal violence that exists in four literary works of heroic character, dating from different periods and places: the Greek Odyssey, the Japanese Heikemonogatari, the Hispanic ballad of The Moorish king who challenges Valencia, and the epic of Gorba Dikko sung by the Djerma people of Niger. Important conclusions are drawn about the poetics of epics and of epic ballads.